Superação do precedente judicial nos tribunais superiores: pressupostos materiais e processuais - Figueiredo, Luciana Monduzzi (2020)
The thesis aims to establish parameters for judicial precedent overruling in Brazilian superior courts, with the realistic view that the absence of criteria for changing jurisprudential understanding or legal thesis causes clear legal uncertainty in Brazil. The lack of systematization on the subject shows two problems in the same origin: on the one hand, arbitrary jurisprudential revisionism; and, on the other, the immobilization of changes in judicial interpretation, even if necessary, an indispensable element for the natural process of conformation of law to social reality. The Civil Procedure Code started the construction of a precedent Brazilian system, with the establishment of binding (from which it emanates obligatory) and non-binding (from which it emanates compliance) decision-making standards. The thesis specifically addresses the activity of the Federal Supreme Court and the Superior Court of Justice, higher courts, which have as their vectors the duties of unity, stability, coherence and integrity, conferring a presumption of correctness of precedent. With this premise, the thesis concludes that judicial precedent overruling is only authorized if it does not conform with the legal integrity, in consequence of social incongruence or systemic inconsistency. Based on this binomial, the thesis establishes the material assumptions (determinant causes) for overruling, verified in the obsolescence or error of the precedent, besides the procedural assumptions for the achievement of the purpose, which, among other elements, imposes qualified motivation to the superior courts, with double argumentative burden, under invalidity of the overruling decision